Leptin receptor (LEPR) SNP polymorphisms in HELLP syndrome patients determined by quantitative real-time PCR and melting curve analysis - Than Nándor; Molvarec Attila; Lázár Levente; Várkonyi Tibor; Rigó János; Nagy Bálint (BMC, 2010)
Abstract Background Several studies have shown overexpression of leptin in microarray experiments in pre-eclampsia (PE) and in hemolysis, elevated liver enzymes, low platelets (HELLP) syndrome. We decided to study four leptin receptor (LEPR) SNP polymorphisms in HELLP syndrome patients by using quantitative real-time PCR and melting curve analysis. Methods DNA was isolated from blood samples from 83 normotensive pregnant women and 75 HELLP syndrome patients. Four SNPs, LEPR c.326A>G (K109), LEPR c.668A>G (Q223R), LEPR c.1968G>C (K656N) and LEPR c.3024A>G (S1008) were determined by quantitative real-time PCR and melting curve analysis. Investigators were blinded to clinical outcomes. Results LEPR c.326A>G, LEPR c.668A>G, LEPR c.1968G>C and LEPR c.3024A>G allele, genotype and haplotype polymorphisms were not different in HELLP syndrome patients and normotensive healthy pregnants. There were strong linkage disequilibrium (LD) between loci c.326A>G and c.6687A>G (D' = 0.974), and c.668A>G and c.1968G>C (D' = 0.934), and c.326A>G and c.1968G>C (D' = 0.885), and c.1968G>C and c.3024A>G (D' = 1.0). However, linkages of c.3024A>G with c.668A>G (D' = 0.111) and c.326A>G (D' = 0.398) were weak. The Hardy-Weinberg equilibrium was observed for all polymorphisms. However the LEPR c.326A>G AG genotype was twice more frequent and the (AG AG GG AG) haplotype was three times more frequent in HELLP syndrome patients. The introduced quantitative real-time PCR combined with melting curve analysis is a fast and reliable method for the determination of LEPR SNPs. Conclusion Although certain LEPR haplotypes are more frequent in HELLP syndrome, we conclude that there is no compelling evidence that the four studied LEPR SNP polymorphisms associated with the development of HELLP syndrome.